2012
DOI: 10.1097/qad.0b013e32834dc593
|View full text |Cite
|
Sign up to set email alerts
|

Influence network effectiveness in promoting couples’ HIV voluntary counseling and testing in Kigali, Rwanda

Abstract: Objective To identify predictors of promotion of couples’ voluntary counseling and testing (CVCT) in Kigali, Rwanda Design Analysis of CVCT promotional agent (influential network leaders, INLs; influential network agents, INAs), and couple/invitation-level predictors of CVCT uptake. Methods Number of invitations and couples tested were evaluated by INL, INA, and couple/contextual factors. Multivariable logistic regression accounting for two-level clustering analyzed factors predictive of couples’ testing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 30 publications
4
39
1
Order By: Relevance
“…The high reported levels of HIVrelated communication are encouraging and suggest the normalisation of HIV (Zuch & Lurie, 2012). Consistent with previous published research, we observed higher levels of MPI among participants who reported higher levels of communication with partners (Ditekemena et al, 2012;Kalembo et al, 2012;Reece et al, 2010) and stable relationship status (Ditekemena et al, 2012;Larsson et al, 2010;Morfaw et al, 2013). The high reported levels of MPI overall indicate that gender norms may be shifting, with men becoming more involved in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high reported levels of HIVrelated communication are encouraging and suggest the normalisation of HIV (Zuch & Lurie, 2012). Consistent with previous published research, we observed higher levels of MPI among participants who reported higher levels of communication with partners (Ditekemena et al, 2012;Kalembo et al, 2012;Reece et al, 2010) and stable relationship status (Ditekemena et al, 2012;Larsson et al, 2010;Morfaw et al, 2013). The high reported levels of MPI overall indicate that gender norms may be shifting, with men becoming more involved in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Documented barriers to MPI include poor communication within couples (Ditekemena et al, 2012;Kalembo, Yukai, Zgambo, & Jun, 2012;Reece, Hollub, Nangami, & Lane, 2010), less stable relationship status (Larsson et al, 2010;Morfaw et al, 2013) and traditional gender roles (Nkuoh et al, 2010;Reece et al, 2010;Theuring et al, 2009), including the belief that antenatal care is purely a women's responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…This model was successful, particularly when invitations were distributed to the homes of individuals known personally to the INA, accompanied by an INL public endorsement, and with the availability of a mobile testing unit. 42,43 …”
Section: Introductionmentioning
confidence: 99%
“…Several strategies, such as partner notification and community invitations have been effective for increasing cHCT and could have important implications if brought to scale. [39][40][41] Such efforts would have benefits on reduced HIV incidence and on reaching global HIV targets, including the 90-90-90 goals and elimination of mother-to-child transmission [42][43][44] Assessing the impact of HCT on HIV acquisition is methodologically challenging. First, all assessments of HIV acquisition require large cohorts followed for long periods with low, nondifferential loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%